FASILITAS DUDUK DI AREA PUBLIK TAMAN KOTA DAN PLAZA GEDUNG PERKANTORAN - Setiadi GS (Jurnal Dimensi Seni Rupa dan Desain, 2013)
Abstract Par and rest area are inseperable from human's need to simply sit down and socialize . Although seats in Indonesia have develoved quite far, if wasn't actually originate in Indonesia. Originally, Indonesia traditional houses are " Rumah Panggung" with every day activities conduct oh the flour. " Budaya Melantai" such as dinning, sleeping, consiercing the existences of seat. They was built on stilts and people went about their daily activities, such as eating and sleeping, on the floor. It was the European settlers that first introduced chairs to Indonesia.  Abstraktaman dan sarana fasilitas duduk bagian yang tidak terpisahkan dengan kebutuhan manusia untuk duduk dan melaksanakan interaksi sosial. Di tengah perkembangan berbagai macam fasilitas dduk, jenis kursi di Indoensia, sarana tersebut di Indonesia tidak memiliki sejarah tentang kursi di Indonesia. Rumah-rumah tempo dulu di indoensia todak memiliki kursi. Pada zaman dahulu rumah-rumah di Indoensia adalah berupa rumah panggung dan memiliki budaya melantai.